Proposal to add a Note to Rule 8 of the International Code of Nomenclature of Prokaryotes to clarify the meaning of the term ‘stem’ - Oren, Aharon; Kostovski, Marko; Pallen, Mark J (Microbiology Society, 2024)
According to the Rules of the International Code of Nomenclature of Prokaryotes (ICNP) and its appendices, names of higher taxa are formed by the addition of the appropriate suffix to the stem of the name of the type genus, and word stems derived from Latin and/or Greek are combined to compound names by means of an appropriate connecting vowel. The way the word ‘stem’ is used in the ICNP differs from the meaning of this term in textbooks of Latin and Greek grammar. We therefore propose to add a Note to Rule 8, clarifying that the term ‘stem’ when used in the ICNP corresponds with that part of the word that does not vary among the forms of the noun in the oblique cases, i.e., cases other than the nominative, and which can be obtained by deleting the ending of the genitive singular.
Keywords: compound names; International Code of Nomenclature of Prokaryotes; word stems